Preparation and evaluation of aqueous phase compatible molecularly imprinted polymers for shikimic acid - Yeoh, Chee Beng (2015)
Shikimic acid (SA) is an important component in the production of several important drugs particularly the anti-influenza drug, Oseltamivir. Naturally, SA exists as an intermediate in the plant biosynthesis of aromatic compounds via shikimate pathway. Commercially, SA is extracted from the Chinese star anise or produced through the fermentation process by modified strain of Escherichia coli (E. coli). Regardless of the method of production, SA needs to be purified before it can be used for the intended purpose. Conventional method in the purification of SA usually involved the use of non-specific adsorbents that are less effective in isolating the SA. Molecularly imprinted polymer (MIP) being one of the latest adsorbents in separation science, offers an alternative technique that is more selective and specific than the conventional adsorption methods. MIP is known to be not compatible to the aqueous phase with usually low or no selectivity, making the preparation of MIP that work well in aqueous phase a challenge to those in the field. Reported in this thesis are exploratory work carried out to prepare non-covalent imprinted polymer for SA with the aim that the polymer prepared is capable of working in highly aqueous environment in which the raw extract of SA is usually in. “Trial and error” approach was used as the preliminary tool in searching the right formulation of template:monomer:cross-linker (TMX) ratio that produced a good imprinted polymer judging from the imprinting factor (IF) scores of the polymer in batch rebinding experiments. The optimized TMX ratio finally determined was 1:6:10 in 10 mL methanol and water (4:1, v/v) porogen system. The best template: monomer (TM) ratio was also evaluated using ultraviolet (UV) spectroscopy approach, the results obtained were in agreement with the preliminary “trial and error” results, indicated that TM ratio of 1:6 was the optimal. The polymer was physically characterized using Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) techniques. Results indicated that complete polymerization was achieved and different morphologies observed between imprinted and control polymers may be used to explain the imprinting effect shown by the SA imprinted polymer. Optimization on the rebinding conditions suggested that the SA imprinted polymer performed best in 100% aqueous environment at pH 4.0. Binding isotherm study suggested that the binding sites distribution was heterogeneous in nature and it can be well described using Freundlich isotherm model. Study of the polymer’s adsorption kinetic concluded that the adsorption process obeyed pseudo second order kinetic with rate constant, K of 0.0047 gmg-1min and the experimental maximum adsorption for SA imprinted polymer was determined as 38.8 mgg-1. Cross-reactivity experiments results showed that the imprinted polymer having good selectivity toward SA and the polymer was packed into cartridge and used for the separation of SA from artificial mixture of SA, methyl shikimate (SE) and gallic acid (GA) in tap water. A clean separation with three isolated peaks as shown in high performance liquid chromatography (HPLC) chromatogram was obtained.